Receptores similares a Toll en peces: el inicio de la divergencia - Rondón Barragán, I.S. (2009)
Innate immunity initiates mechanisms based on the non-clonal recognition of microbial components, so-called PAMPs by using a variety of gene-encoded pattern recognition receptors (e.g. toll-like receptors). PAMPs are essential structures for the physiology and survival of the microbes. Toll-like receptors are transmembrane receptors family type I, with an aminoterminal leucin-rich repeat domain and a carboxiterminal intracellular tail; which are expressed in cells such as neutrophils, macrophages, dendritic cells, as well as others. Activation pathways including the recruitment of cytoplasmic adaptor proteins that activate kinases and tumor necrosis factor- associated factors, lead to the activation of nuclear factors and the cytokine production and surface co-stimulatory molecules expression in antigen-presenting cells. The knowledge about Toll-like receptor allows both the understanding of immune response dynamic and the processes involved in the recognition of microbial agents. This review focuses on the identification of several fish Toll-like receptor, them functions and them interactions with others as well as the homology and identity in animals.\n